Results of the fiscal control activity in Romania and other European States - Genifera Claudia Bănică (UTMS Journal of Economics, 2022)
The article addresses the organization and results of the fiscal control activity in Romania. The forms of fiscal control exercised in Romania are presented, respectively: general, partial, total or selective fiscal control. They were compared to the data provided for 2017 by the tax administration report by the OECD from 9 countries (Greece, Italy, Spain, United Kingdom, France, Portugal, Germany, Austria and Denmark), in terms of tax control activity. The results obtained from the mentioned states indicate in Romania a low degree of tax collection as a result of the established additional fiscal obligations. As measures to improve the fiscal control activity in Romania, we mention the amendment of the Civil Servant Statute, by hiring only staff with at least 3 years of experience in the field of accounting for training and verification of mandatory financial statements to individuals or legal entities. The efficiency of the fiscal inspection activity can take place by emphasizing the electronic control, to the detriment of a classic fiscal inspection, but also by intensifying the general control.
Keywords: G32; H11; H21; 330; additional obligations; selective fiscal; government performance; fiscal damage; general control